On new subclasses of analytic functions involving generalized differential and integral operators (European Journal of Pure and Applied Mathematics, 2011)
We define a generalized differential and integral operators on the class A ofanalytic functions f(z) = z +P1n=2anzn in the unit disk U:= {z2C:|z|